Perbedaan pendapatan usahatani Minapadi dan non Minapadi pada lahan sawah tadah hujan di Kabupaten Konawe Selatan - Fyka, Samsul Alam (Universitas Halu Oleo, 2023)
Lowland rice farming based on the Minapadi and non-Minapadi systems has The study aims to determine the difference in income between Minapadi and non-Minapadi farming businesses. The study was conducted in 2022 at the Minapadi development center, namely Epeesi Village. The study uses a survey method. The study location was chosen purposively. Sample determination was carried out using a non-probability sampling method using quota sampling techniques. The total sample was 60 respondents, including 30 respondents for farmers who implemented Minapadi farming and 30 respondents for farmers who implemented non-Minapadi farming. The variables in this study are farming production costs, revenues, selling prices, production and income from Minapadi and non-Minapadi farming. The data analysis used is the independent samples t-test. The results of the study show that minapadi farming income is IDR 12,734,348,-/ha/MT, while non-minapadi farming income is IDR 6,331,289,-/ha/MT, with an income difference of IDR 6,403,059,-/ha/MT. Meanwhile, the results of the independent sample t-test analysis show a difference in income between Minapadi farming and non-Minapadi farming. Keywords: comparative; Minapadi; rainfed; independent samples t-test